The therapeutic potential of PROTACs. (2nd January 2021) - Benowitz, Andrew B.; Jones, Katherine L.; Harling, John D.
ABSTRACT: Introduction: PROTACs represent a novel class of heterobifunctional molecules that simultaneously bind to a target protein and to an E3 ligase complex, resulting in the transfer of ubiquitin and initiating a process ultimately causing the proteasomal degradation of the target protein. This mechanism of action imbues PROTACs with the ability to modulate target biology in unique ways compared to inhibitors, and the development of PROTACs as therapeutic agents is expected to result in new medicines to treat multiple diseases. Areas covered: This review includes published PCT (WO) patent applications covering January 2013 through June 2020. Only English-language patent applications with exemplified PROTACs reported to degrade a target protein(s) were deemed in scope, and the definition of 'PROTAC' was restricted to a bifunctional molecule which contains a discrete binding element for a specific degradation target(s), as well as a separate discrete E3 ligase-binding moiety. Expert opinion: Delivering on the enormous potential of PROTACs will require the development of PROTAC medicines that are differentiated from traditional small-molecule inhibitors. The modular composition of PROTACs affords both opportunities and challenges in securing robust intellectual property, and we envision that requirements for novelty are likely to evolve as this area matures.